2023
DOI: 10.3390/ijerph20021545
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Behavioral Factors Involved in Temporomandibular Myalgia and Migraine: Common but Differentiated Profiles

Abstract: Background: Many studies have revealed high comorbidity and a clear association between temporomandibular disorders (TMD) and migraine. Furthermore, evidence points out that common psychological and behavioral factors might be related to the observed TMD and migraine association. However, this association and the underlying psychological factors are poorly understood. Objective: The main goal of this study was to describe the psychological and behavioral factors involved in TMD myalgia and migraine. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…One recent research, utilizing the same factorial design as our study, found elevated anxiety and somatization in TMD patients and greater anxiety, depression, and somatization in migraineurs. 43 Our results are in full agreement with these findings, as we also observed an across-group gradient (HC < TMD < MIG < TMD+MIG) of increasing estimates for all four psychological factors assessed. Additionally, our analysis also showed a more pronounced association of anxiety, depression, stress, and somatization with migraine than with painful TMD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One recent research, utilizing the same factorial design as our study, found elevated anxiety and somatization in TMD patients and greater anxiety, depression, and somatization in migraineurs. 43 Our results are in full agreement with these findings, as we also observed an across-group gradient (HC < TMD < MIG < TMD+MIG) of increasing estimates for all four psychological factors assessed. Additionally, our analysis also showed a more pronounced association of anxiety, depression, stress, and somatization with migraine than with painful TMD.…”
Section: Discussionsupporting
confidence: 92%
“…One recent research, utilizing the same factorial design as our study, found elevated anxiety and somatization in TMD patients and greater anxiety, depression, and somatization in migraineurs. 43 Our results are in full agreement with these findings, as we also observed an across-group gradient (HC < TMD < MIG < TMD+MIG) of…”
Section: Comparison Of Psychological and Somatosensory Profiles Of Tm...supporting
confidence: 92%
“…Additionally important is the absence of a control group or a placebo group to compare with the evolution of the process or with other interventions. The authors also recognize as a limitation the fact that they did not measure the psychological and behavioral factors of the sample analyzed in the study, which is observed as a determinant in different chronic diseases [ 24 , 25 ]. Although there is an inherent bias in the type of research model, this has been minimized by using relevant and reliable human (accredited clinical experience of the researchers) and instrumental resources.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can be biological, behavioral, psychosocial, but also previous chronic pain conditions and trauma are important risk factors. It has been suggested that one of the most important factors to develop TMD is other somatic symptoms ( 27 ). For instance, patients with fibromyalgia have a higher prevalence of TMD symptoms ( 28 ).…”
Section: Etiologymentioning
confidence: 99%